1998
DOI: 10.1109/92.661245
|View full text |Cite
|
Sign up to set email alerts
|

Overview of complementary GaAs technology for high-speed VLSI circuits

Abstract: A self-aligned complementary GaAs (CGaAs TM) technology developed at Motorola for low-power, portable, digital and mixed-mode circuits is being extended to address highspeed VLSI circuit applications. The process supports full complementary, unipolar (pseudo-DCFL), source-coupled, and dynamic (domino) logic families. Though this technology is not yet mature, it is years ahead of CMOS in terms of fast gate delays at low power supply voltages. Complementary circuits operating at 0.9V have demonstrated power-dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 1989, Kiehl and colleagues at IBM designed and fabricated a single heterostructure that included both n-and p-channel GaAs layers with AlGaAs barriers, and demonstrated p-channel FETs operating at 77 K [1]. A decade later, a group at Motorola formed adjacent n-and p-channel GaAs FETs using ion implantation and demonstrated digital circuits [2]. More recently, Leuther et al demonstrated room-temperature ring oscillators using complementary n-and p-FETs with separate InGaAs channels and Al(Ga)As barriers grown in a single heterostructure [3].…”
Section: Heterostructure Designmentioning
confidence: 98%
“…In 1989, Kiehl and colleagues at IBM designed and fabricated a single heterostructure that included both n-and p-channel GaAs layers with AlGaAs barriers, and demonstrated p-channel FETs operating at 77 K [1]. A decade later, a group at Motorola formed adjacent n-and p-channel GaAs FETs using ion implantation and demonstrated digital circuits [2]. More recently, Leuther et al demonstrated room-temperature ring oscillators using complementary n-and p-FETs with separate InGaAs channels and Al(Ga)As barriers grown in a single heterostructure [3].…”
Section: Heterostructure Designmentioning
confidence: 98%
“…One GaAs logic family, complementary heterostructure field effect transistor technology (C-HIGFET or C-HFET), 78 appears promising for space-based applications. C-HFET technology exhibits SEU cross sections that are one to two orders of magnitude lower than either Si emitter coupled logic or GaAs MESFET alternatives, 79 while maintaining the high speed and total ionizing dose immunity that are characteristic of GaAs.…”
Section: Single-event Effects In Gaas Devices and Circuitsmentioning
confidence: 99%
“…CGaAs has some design challenges, including higher gate and source-drain leakage currents than comparable CMOS processes [3]. As in CMOS, many logic styles can be realized in CGaAs, including Complementary, Source-Coupled FET Logic (SCFL), Domino, Dual-Rail Domino, Differential Cascode Voltage Switch Logic (DCVSL), and Pseudo-Direct Coupled FET Logic (P-DCFL) [3].…”
Section: Cgaas Overviewmentioning
confidence: 99%
“…As in CMOS, many logic styles can be realized in CGaAs, including Complementary, Source-Coupled FET Logic (SCFL), Domino, Dual-Rail Domino, Differential Cascode Voltage Switch Logic (DCVSL), and Pseudo-Direct Coupled FET Logic (P-DCFL) [3]. We evaluated Domino logic through the design of a PowerPC ALU [1], and DCVSL through the design of a multiplyaccumulate unit [7].…”
Section: Cgaas Overviewmentioning
confidence: 99%